Synergistic effects of Ferula gummosa and radiotherapy on induction of cytotoxicity in HeLa cell line - Seyed Hamid Forouzmand; Seyed Hadi Mousavi; Vahid Vazifedan; Mahnaz Nourbakhsh; Jamshidkhan Chamani; Azar Hoseini; Azar Fani Pakdel (Mashhad University of Medical Sciences, 2018)
Objective: Cervical cancer is the second most common type of cancer among women, worldwide; and for treatment of this type of cancer radiotherapy is commonly used. Ferula gummosa Boiss("Barije" in Persian, from the family Apiaceae), (F. gummosa), is an extremely precious medicinal plant which naturally grows throughout the Mediterranean and Central Asia and is a native plant in Iran. The present study examined the cytotoxic effects of F. gummosa in terms of induction of apoptosis and radiosensitivity in HeLa cells. Materials and Methods: In order to determine F. gummosa cytotoxicity in HeLa cells, the cells were incubated with different concentrations of the plant resin(0-1000 µg/ml) for 24, 48 and 72 hr. Cytotoxicity was determined by MTT assay. The role of apoptosis in F. gummosa cytotoxicity was investigated using flow cytometry following propidium iodide (PI) staining of DNA. For radiosensitivity assessment, F. gummosa-treated cells were exposed to 2 Gy γ-rays, and cytotoxicity was determined in irradiated and non-irradiated (control) groups by MTT and the synergism factor was calculated. Results: F. gummosa decreased cell viability in HeLa cells in a concentration- and time-dependent manner. Flow cytometryanalysisindicated that apoptosis is involved in F. gummosa-induced cytotoxicity. Co-administration of F. gummosa and radiotherapy, showed that this plantat non-toxic low doses, could result in almost 5-fold increment in sensitization of cells towards radiation-induced toxicity. Conclusion: The concurrent use of F. gummosa and radiation increases radiosensitivity and cell death. Therefore, F. gummosa can be considered as a potential radiosensitizer agent against cervical cancer.